2019
DOI: 10.1159/000496699
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in the Treatment of Endometrial Cancer: Why We Fail? Results of a Prospective Multicenter Study on the Factors Associated with Failure of Node Mapping with Indocyanine Green

Abstract: Background: The sentinel lymph node (SLN) mapping for endometrial cancer staging is gaining wide diffusion, but there is no definitive evidence on the factors associated with the failure of mapping. Objectives: To analyze the factors associated with the possible failure of bilateral SLN mapping with indocyanine green (ICG). Methods: A prospective observational study without control on 110 patients with endometrial cancer apparently confined to the uterus, underwent laparoscopic surgical staging with SLN mappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…The latter factor has been associated with successful bilateral mapping by some authors. The results of the study performed by Ianieri M. et al, showed that the surgeon was the only independent factor associated with the success of SLB [20]. As mentioned previously, the overall and bilateral detection rate in our study tended to increase with the experience as well and could be considered in agreement with this statement.…”
Section: Discussionsupporting
confidence: 92%
“…The latter factor has been associated with successful bilateral mapping by some authors. The results of the study performed by Ianieri M. et al, showed that the surgeon was the only independent factor associated with the success of SLB [20]. As mentioned previously, the overall and bilateral detection rate in our study tended to increase with the experience as well and could be considered in agreement with this statement.…”
Section: Discussionsupporting
confidence: 92%
“…Ianieri et al . demonstrated that the only risk factor associated with the failure of SLN mapping was the human factor, that is, the surgeon . In the current case report, failure of SLN mapping in a patient with endometrial cancer with a 12‐year history of CLL may be related with obstruction of lymphatic flow.…”
Section: Discussionmentioning
confidence: 65%
“…Much effort still must be made to minimize the false negative detection rate. The objective of the study of Ianieri et al, was to analyse factors associated with possible failure of bilateral SLN mapping with the use of ICG [24]. The authors evaluated different clinical (age, body mass index, menopausal status, previous history of pelvic surgery), pathological (tumor histology, diameter, clinical stage, lymphovascular space invasion status), and institutional (surgeon's experience and technical ability) factors that could be associated with unsuccessful SLN mapping procedure.…”
Section: Detection Rates and Localizations Of Slnmentioning
confidence: 99%
“…The authors evaluated different clinical (age, body mass index, menopausal status, previous history of pelvic surgery), pathological (tumor histology, diameter, clinical stage, lymphovascular space invasion status), and institutional (surgeon's experience and technical ability) factors that could be associated with unsuccessful SLN mapping procedure. Based on the multivariate analysis, the only significant factor associated with the success of bilateral SLN mapping was the surgeon's technical ability and experience [24]. SLN detection rates increase with number of procedures performed.…”
Section: Detection Rates and Localizations Of Slnmentioning
confidence: 99%